Genetic diversity in spring faba bean (Vicia faba L.) genotypes as revealed by high-throughput KASP SNP markers - Mulugeta, B.; Tesfaye, K.; Keneni, G.; Ahmed, S. (Springer, 2021)
Faba bean is one of the oldest legume crop grown around the world for its cheap source of protein and for being used in crop rotation with cereals to improve soil fertility through nitrogen fixation. This study was designed to determine the extent and pattern of genetic diversity and relationships among 48 Ethiopian faba bean genotypes using 37 SNPs loci based on Kompetitive allele specific PCR SNP markers. Thirty-six SNPs were found polymorphic and revealed an average of 95.6% polymorphisms. The gene diversity ranged from 0.16 to 0.50 with a mean of 0.42 and the PIC value ranged from 0.14 to 0.38 with a mean of 0.33. The Bayesian clustering model grouped the genotypes into two genetically distinct clusters with certain degree of admixture, indicating the introduction of chromosomes of different ancestry and allele frequency. The result clearly showed the presence of relatively high genetic diversity among faba bean genotypes grown in Ethiopia. Thus, these genotypes can be used in faba bean breeding programs to develop farmer preferred cultivars with desirable traits.